Update of Religion Studies Teaching as an Important Factor of Bringing up Spirituality and Tolerance of Students, Professional Training of Elementary-Level Education Specialists - Blazhevych, Yuriy (Pedagogical Discourse, 2012)
In the article on the basis of study of recent researches and publications of domestic and foreign scholars the author highlights the problem of updating the teaching of religion studies as an important factor of bringing up spirituality and tolerance of students and professional training of elementary-level education specialists